SOMATOTYPE PENJAGA GAWANG UNIT KEGIATAN MAHASISWA SEPAKBOLA UNY TAHUN PELATIHAN 2010/2011 - Nawan Primasoni; Sulistiyono Sulistiyono (Jorpres (Jurnal Olahraga Prestasi), 2016)
This research aims to know goal keeper somatotype of college student soccer center member of Yogyakarta State University 2010. This research is a survey research.The population in this research is all goal keepers who are the member of college student soccer center of Yogyakarta State University in the coaching year of 2010. The sample of the population was taken by total sampling. It got 11 goal keepers as the sample of this research. The research instrument used in this research was somatotype test according to heat-charter. Data analysis used in this research was percentage. The result showed that most of the goal keepers of college student soccer center in Yogyakarta State University were ectomorph mesomorph type with 54% in percentage. Keywords: somatotype, goal keeper